"Not a hair of your head will perish" (Luke 21:18) Jesus' Eschatological Poetics and the faith in God's providence - Martos, Balázs Levente (Concilium, 2023)
In September 2022, in a Contemporary Art Gallery in Budapest, I was captivated by the view of a strange artifact. Two ceramic plates, forming a pair of grape leaf, one alongside the other, with short phrases written on their greenish surface. As I stepped closer, the phrases revealed quotes from the Gospel of Luke, chapter 21. They were reassuring sayings of Jesus about the help of God in very difficult times, in fact, in times of hardship, war, and suffering. Why are those grape leaves, greenish, but also yellow and brown, as if in the time of grape harvest, at some points also broken, as if already dry? Allusions for the final time, for a time, when the end will be near, when the whole world will be waiting for something new to come, are at hand. But what about those phrases from the Gospel? How should I understand the phrases of Jesus written on something so perishable? Is it not also our faith, which is so dry and dying, as those dry leaves? Aren't we, Christians of the XXI. century, wearing the promises of Jesus, and yet, not living out of them, like leaves, fallen from trees, driven by wind, as Isaiah put it (cf. Isa 34:4; 64:5)?